Analisis Tingkat Keprofesionalan Guru Berdasarkan Kompetensi Guru - Hasriyati Harahap; Rahmad Ali Tanjung; Intan Syahvitri; Hasbih Soleh Suryadi; Abdul Halim Seregar; Madila Shinta Rantika (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to find out or obtain a description of the competence of a teacher who teaches at SMP Taman Siswa, Medan. The method used in compiling this research is a descriptive qualitative approach. Data collection techniques using interview techniques. The interview technique with descriptive analysis stated the results that:1) a teacher is able to understand how the characteristics that exist in each student well. 2) the understanding of a teacher in bringing and delivering the material or material that will be brought to the subject on that day is categorized well. 3) a teacher can be said to be a professional teacher, because he is able to teach well and teach according to his position or placement.